Current state of Czech andragogy - Jan Průcha (Czech Pedagogical Society, 2010)
The survey article should serve as an information for educationists about thesituation of andragogy (theory and research of adult education) in the Czech Republic.First, a brief explanation is presented based on definitions of andragogy and its mainthemes. The second part describes centres of andragogy in five Czech universities.Later on, an overview of main publications of Czech andragogy is given with respectof their relevance for educationists. Finally, some weak features of Czech andragogy arementioned, especially a lack of empirical research of adult education and learning. Thisis just an area in which some methods of educational research can be usefully applied.